MANAJEMEN SARANA DAN PRASARANA UNTUK MENINGKATKAN MUTU PENDIDIKAN DI SMK NEGERI 1 SINTANG - Yuniawan, Putut Jatmiko; Wahyudi, Wahyudi; Chiar, M (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe purposes of this research is to reveal Management of Educational Facilities Infrastructure to Improvement Educational Quality of SMK Negeri 1 Sintang. The research method used qualitative research with descriptive approach. Data collected by in-depth interviews, participant observation, Â documentation and analyzed by data reduction, data presentation, conclusion or verification. Testing of data reliability is done by extending the observation period, and triangulation. The results of the study concluded : (1) planning of the facilities and infrastructure programs had been made by the student section to develop the facilities in the activities at the school. (2) The use of facilities and infrastructure is carried out in accordance with the learning needs of each teacher and arranged and monitored in an orderly manner, (3) Monitoring of facilities and infrastructure has been carried out directly by the principal, (4) Reporting has been carried out periodically by the student head school, (5) Obstacles faced in facilities and infrastructure are financing for procurement and maintenance. Based on the results of the study it is suggested the following matters: (1) The principal is expected to optimize the supervision of all planned activities so that the objectives that have been determined can be achieved. (2) It is necessary to involve the community in providing financing and maintenance of facilities and infrastructure. (3) Teachers, administration is expected to be involved in the management of facilities and infrastructure.Keywords: Educational quality, Facilities, infrastructure, Managing educational.